A Calculation Model for Serum Ionized Calcium Based on an Equilibrium Equation for Complexation - Takano, Susumu (Libertas Academica, 2012)
Measurement of ionized calcium is more important than measurement of total calcium in serum samples. In the present study, equations were derived from complexation and acid dissociation equilibrium equations, and were used to determine the concentration of ionized calcium from the observed serum concentrations of total calcium, albumin, total protein, and inorganic phosphate. The ionized calcium concentration was calculated in 67 serum samples from healthy subjects and 34 outpatients previously identified as having abnormal serum calcium levels. The correlation coefficient between our method (y) and the calcium-ion-selective electrode method (x) was 0.953 and the linear regression equation was y = 0.97x at pH 7.4 with a factor of α = 0.21, which was based on the differences between the concentrations of calcium phosphorus compounds obtained by the electrode method and by calculation. The developed calculation is as useful and accurate as the electrode method, and therefore extremely useful for clinical diagnoses.